Estudo e desenvolvimento de um capacitor eletrolítico de nióbio - Cerniak, Samuel Nogueira (2012)
It seeks to find an alternative to the current tantalum electrolytic capacitors in the market due to its high cost. Niobium is a potential substitute, since both belong to the same group of the periodic table and because of this have many similar physical and chemical properties. Niobium has several technologically important applications, and Brazil has the largest reserves, around 96%. There are including niobium in reserves of tantalite and columbite in Rio Grande do Norte. These electrolytic capacitors have high capacitance specifies, ie they can store high energy in small volumes compared to other types of capacitors. This is the main attraction of this type of capacitor because is growing demand in the production of capacitors with capacitance specifies increasingly high, this because of the miniaturization of various devices such as GPS devices, televisions, computers, phones and many others. The production route of the capacitor was made by powder metallurgy. The initial niobium powder supplied by EEL-USP was first characterized by XRD, SEM, XRF and laser particle size, to then be sieved into three particle size, 200, 400 e 635mesh. The powders were then compacted and sintered at 1350, 1450 and 1550°C using two sintering time 30 and 60min. Sintering is one of the most important parts of the process as it affects properties as porosity and surface cleaning of the samples, which greatly affected the quality of the capacitor. The sintered samples then underwent a process of anodic oxidation, which created a thin film of niobium pentóxido over the whole porous surface of the sample, this film is the dielectric capacitor. The oxidation process variables influence the performance of the film and therefore the capacitor. The samples were characterized by electrical measurements of capacitance, loss factor, ESR, relative density, porosity and surface area. After the characterizations was made an annealing in air ate 260ºC for 60min. After this treatment were made again the electrical measurements. The particle size of powders and sintering affected the porosity and in turn the specific area of the samples. The larger de area of the capacitor, greater is the capacitance. The powder showed the highest capacitance was with the smallest particle size. Higher temperatures and times of sintering caused samples with smaller surface area, but on the other hand the cleaning surface impurities was higher for this cases. So a balance must be made between the gain that is achieved with the cleaning of impurities and the loss with the decreased in specific area. The best results were obtained for the temperature of 1450ºC/60min. The influence of annealing on the loss factor and ESR did not follow a well-defined pattern, because their values increased in some cases and decreased in others. The most interesting results due to heat treatment were with respect to capacitance, which showed an increase for all samples after treatment